Peran Pendidik dan Lembaga Pendidikan dalam Membentuk Kesalehan Individu (Studi Perspektif Normatif) - Mulyani; Melisa; Risman Bustamam (STAI Terpadu Yogyakarta, 2021)
This study aims to find out the role of educational institutions and educators in shaping individual mistakes. This research uses a qualitative approach based on literature study. The results of this study indicate that educators in the sense of being nurtured and imitated have a very large role in shaping the morality of students to become a pious generation. Educators and students as a unit that has an attachment to each other. Islamic educational institutions need to manage education including educators and students. Educators and students are human resources who have an important role in shaping piety.